Cloning, sequence and expression of the lactate dehydrogenase gene from the human malaria parasite, Plasmodium vivax - Turgut-Balik, D; Akbulut, E; Shoemark, DK; Celik, V; Moreton, KM; Sessions, RB; Brady, RL (Springer, 2004)
Increased drug resistance to anti-malarials highlights the need for the development of new therapeutics for the treatment of malaria. To this end, the lactate dehydrogenase (LDH) gene was cloned and sequenced from genomic DNA of Plasmodium vivax (PvLDH) Belem strain. The 316 amino acid protein-coding region of the PvLDH gene was inserted into the prokaryotic expression vector pKK223-3 and a 34 kDa protein with LDH activity was expressed in E. coli. Structural differences between human LDHs and PfLDH make the latter an attractive target for inhibitors leading to novel anti-malarial drugs. The sequence similarity between PvLDH and PfLDH (90% residue identity and no insertions or deletions) indicate that the same approach could be applied to Plasmodium vivax, the most common human malaria parasite in the world.
Keywords: anti-malarial; gene cloning; homology model; lactate dehydrogenase; Plasmodium vivax